2005
DOI: 10.1128/iai.73.11.7602-7612.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RANTES Promoter Activation in Gastric Epithelial Cells Infected withHelicobacter pylori

Abstract: RANTES, a CC chemokine, plays an important role in the inflammatory response associated with Helicobacter pylori infection. However, the mechanism by which H. pylori induces RANTES expression in the gastric mucosa is unknown. We cocultured gastric epithelial cells with wild-type H. pylori, isogenic oipA mutants, cag pathogenicity island (PAI) mutants, or double knockout mutants. Reverse transcriptase PCR showed that RANTES mRNA was induced by H. pylori and that the expression was both OipA and cag PAI dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…Phosphorylation of JNK and IκB was induced in a time-dependent manner through 18 months, a pattern similar to the activation of NF-κB and ISRE binding. These data agree with results obtained from human gastric cells infected with H pylori, showing that JNK and IκB are involved in upstream NF-κB signaling and that p38 and IκB are upstream of ISRE 4,15,22,26 Immunoblots were used to examine mucosal samples from the 3 groups at 18 months. Levels of phosphorylated ERK were highest in the ulcer group, followed by the gastritis and the atrophy groups (see Supplementary Figure 3A online at www.gastrojournal.org).…”
Section: Immunoblot Analysis Of Mapks and Iκb Pathways In Gastric Mucsupporting
confidence: 87%
See 1 more Smart Citation
“…Phosphorylation of JNK and IκB was induced in a time-dependent manner through 18 months, a pattern similar to the activation of NF-κB and ISRE binding. These data agree with results obtained from human gastric cells infected with H pylori, showing that JNK and IκB are involved in upstream NF-κB signaling and that p38 and IκB are upstream of ISRE 4,15,22,26 Immunoblots were used to examine mucosal samples from the 3 groups at 18 months. Levels of phosphorylated ERK were highest in the ulcer group, followed by the gastritis and the atrophy groups (see Supplementary Figure 3A online at www.gastrojournal.org).…”
Section: Immunoblot Analysis Of Mapks and Iκb Pathways In Gastric Mucsupporting
confidence: 87%
“…In previous in vitro studies using human gastric cancer cell lines, we showed that both p50 and p65 were components of NF-κB binding complexes. 15,22,26 However, because the accuracy of commercially available antibodies against p50 in Mongolian gerbils is unknown, we cannot conclude that p50 was not present.…”
Section: H Pylori Infection Activates Nf-κb Isre Ap-1 and Creb In mentioning
confidence: 93%
“…This result also is consistent with prior studies showing that in gastric epithelial cells, OipA, but not the cag PAI induced the p38 pathway (23,26). To test the hypothesis that OipA plays a role in p38 induction in THP-1 cells, we preincubated cells with chemical inhibitors or DMSO at 37°C for 1 h followed by infection with the oipA mutants.…”
Section: Effect Of Inhibition Of Mapk and Nf-b Pathways On Il-18 Indusupporting
confidence: 73%
“…Importantly, the behavior of gastric epithelial cells and monocytes differed markedly in response to the virulent factors of H. pylori; cag PAI and OipA. Previous studies (23,25,26) have suggested that both cag PAI and OipA were involved in the induction of various cytokines and chemokines in the gastric mucosa, such as IL-6, IL-8, and RANTES cells. Although the relationship between OipA and IL-8 remains unclear in epithelial cells (36), there is agreement that the cag PAI does not play a role in the induction of these cytokines in THP-1 cells (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation